2017
DOI: 10.1002/andp.201700082
|View full text |Cite
|
Sign up to set email alerts
|

From Diffusive to Ballistic Transport in Etched Graphene Constrictions and Nanoribbons

Abstract: Graphene nanoribbons and constrictions are envisaged as fundamental components of future carbon-based nanoelectronic and spintronic devices. At nanoscale, electronic effects in these devices depend heavily on the dimensions of the active channel and the nature of edges. Hence, controlling both these parameters is crucial to understand the physics in such systems. This review is about the recent progress in the fabrication of graphene nanoribbons and constrictions in terms of low temperature quantum transport. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 95 publications
1
11
0
Order By: Relevance
“…For graphene nanoribbons, conductance steps of 4 e 2 /h height are predicted 41 , where the factor of 4 comes from the spin and valley degeneracy of the charge carriers. However, as also reported earlier, graphene constrictions often display 2 e 2 /h conductance steps instead 18,[22][23][24] , attributed to the lifting of the valley degeneracy. This is also predicted by the theoretical calculations of Guimarães et al in which plateau-like features with a spacing of 2 e 2 /h can be observed in graphene nanoconstrictions that are less or equal in length than width (L ≤ W) 42 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…For graphene nanoribbons, conductance steps of 4 e 2 /h height are predicted 41 , where the factor of 4 comes from the spin and valley degeneracy of the charge carriers. However, as also reported earlier, graphene constrictions often display 2 e 2 /h conductance steps instead 18,[22][23][24] , attributed to the lifting of the valley degeneracy. This is also predicted by the theoretical calculations of Guimarães et al in which plateau-like features with a spacing of 2 e 2 /h can be observed in graphene nanoconstrictions that are less or equal in length than width (L ≤ W) 42 .…”
Section: Resultssupporting
confidence: 79%
“…Such requirements can only be met by suspending graphene or encapsulating it between hexagonal boron nitride layers. Only in the best ultra-high mobility devices can the signatures of size quantization be observed, in the form of more or less evenly spaced modulations (kinks) superimposed on the linear conductance [22][23][24][25] . However, in the absence of magnetic field, these plateaus only become well-defined further away from the Dirac point, corresponding to high conductance quanta (typically, σ > 10 e 2 /h).…”
Section: Introductionmentioning
confidence: 99%
“…A step toward further reducing this type of disorder is to encapsulate graphene in hBN, which prevents process‐induced contaminations on the graphene flake, although the edges are still exposed. This results in substrate‐supported devices with reproducibly high electronic quality and enables the observation of quantum phenomena such as quantized conductance in submicron‐structured graphene constrictions …”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, encapsulation of graphene between lattice-matched hBN allowed for the fabrication of reproducible high mobility devices 9 . However, the conductance quatization in such devices based on intercalated graphene was reported to manifest itself in the form of kinks 10,11 . Well-defined conductance plateaus could not be observed because of the roughness of the heterostructure’s edges and the planar structure itself (the latter resulting from the intrinsic dielectric behavior of the hBN films).…”
Section: Introductionmentioning
confidence: 99%
“…11 Electron transport properties of samples of encapsulated graphene show signatures of quantum conductance in form of kinks. 12,13 Yet, the effect of roughness of the structure due to the intrinsic dielectric behavior of the hBN film and the lack of control in the edge-definition of the heterostructures (of paramount importance to reduce edge scattering) have been detrimental for the appearance of well-defined plateaus of conductance. The problem of edge-definition and high roughness values was partially overcome thanks to the definition of GNCs with exfoliated graphene on hydrophobic silicon oxide substrate with the use of hexamethyldisilazane (HMDS).…”
mentioning
confidence: 99%